Inhibition of telomerase causes vulnerability to endoplasmic reticulum stress-induced neuronal cell death. (26th August 2016) - Hosoi, Toru; Nakatsu, Kanako; Shimamoto, Akira; Tahara, Hidetoshi; Ozawa, Koichiro
Highlights: Telomerase inhibitor, BIBR1532, attenuated ER stress resistance in MCF7-TERT cells. TERT was expressed in SH-SY5Y human neuroblastoma cell lines. BIBR1532 enhanced ER stress-induced neuronal cell death of SH-SY5Y cells. Telomerase may enhance vulnerability of ER stress-induced neurodegeneration. Abstract: Endoplasmic reticulum (ER) stress is implicated in several diseases, such as cancer and neurodegenerative diseases. In the present study, we investigated the possible involvement of telomerase in ER stress-induced cell death. ER stress-induced cell death was ameliorated in telomerase reverse transcriptase (TERT) over-expressing MCF7 cells (MCF7-TERT cell). Telomerase specific inhibitor, BIBR1532, reversed the inhibitory effect of TERT on ER stress-induced cell death in MCF7-TERT cells. These findings suggest that BIBR1532 may specifically inhibit telomerase activity, thereby inducing cell death in ER stress-exposed cells. TERT was expressed in the SH-SY5Y neuroblastoma cell line. To analyze the possible involvement of telomerase in ER stress-induced neuronal cell death, we treated SH-SY5Y neuroblastoma cells with BIBR1532 and analyzed ER stress-induced cell death. We found that BIBR1532 significantly enhanced the ER stress-induced neuronal cell death. These findings suggest that inhibition of telomerase activity may enhance vulnerability to neuronal cell death caused by ER stress.